Multinational strategic alliances - Mockler, Robert J. (Wiley series in practical strategy, 1999)
What makes this book so useful is that it covers a broader range of alliances and has more current case studies than other books currently available. In addition, this comprehensive introduction to the subject provides a base of practical 'how-to-do-it' material and specific decision models covering determining strategic fit, negotiating strategic alliances and selecting compatible partners, formulating type and structure of alliances in light of operational fit, and making strategic alliances work. The book also explores other options instead of alliances such as wholly-owned multinational expansion and exporting, and has major sections on understanding and managing cross-cultural diversity, communications and leadership.